Numerical and analytical investigations of heat transfer for a finned tube heat exchanger with ice slurry as cooling medium. (3rd April 2017) - Long, Youwei; Wang, Shugang; Wang, Jihong; Zhang, Tengfei
Abstract : Using ice slurry as cooling medium in HVAC systems has potential due to its high energy capacity. In order to investigate heat transfer characteristics in finned tube cross-flow heat exchangers with ice slurry as a cooling medium, a numerical method with volume of fluid model and an analytical method are applied. The composition of ice slurry considered for analysis is a carrier fluid (9 wt% sodium chloride solution) and ice crystals with mass fraction at 5%–35%. Results from the proposed methods are primarily validated via comparing with the experimental data from the published literature. Both the numerical and analytical results reveal that the ice crystals have a positive effect on heat transfer of the heat exchanger. Heat transfer rate of the heat exchanger increases with the inlet ice mass fraction rising, and then it will reach a relative stable value. It is also found that the heat transfer rate almost increases linearly with the air inlet temperature. In addition, the numerical results of the airflow temperature field reveal that extending the width of the fins at the downstream direction of the airflow is favorable to the heat exchanging performance of the ice slurry finned tube heat exchanger. Finally, it is beneficial for the analytical method to obtain reliable results when the ice mass fraction difference between the ice slurry inlet and outlet remains no more than 8%.